MENGEMBANGKAN KEMAMPUAN LITERASI MATEMATIS SISWA MELALUI PENGGUNAAN MODUL BERBASIS PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) BERNILAI BUDAYA - Nisvu Nanda Saputra; Prahesti Tirta Safitri; Aan Subhan Pamungkas (Universitas Sultan Ageng Tirtayasa, 2021)
This study looked at students' literacy skills by using modules based on realistic mathematics education (RME) approaches of cultural value. The use of modules in learning that are developed according to the needs of students can help students in learning to develop student literacy skills, the modules used have been through validation tests and effectiveness tests so that they can be implemented to students, the design of this research is non equivalent control group design, which consists of control classes and experimental classes. From the results of the research, it is known that the use of modules based on rme approach is culturally valuable, can improve students' literacy ability by 78% which can be classified as effective